Efeitos neurocomportamentais e neuroquímicos da clorpromazina e clozapina no modelo de esquizofrenia induzido pela cetamina em camundongos - Sampaio, Luis Rafael Leite (2011)
Schizophrenia is a serious and debilitating chronic mental disease, affecting about 1% of the world population and whose symptoms can be induced by ketamine. In this sense, evidences show that oxidative stress has an important role in the pathogenesis of this condition. Thus, this study evaluated the neurobehavioral and neurochemical effects, through the dosage of oxidative stress, after acute administration of Chlorpromazine (Cp) or Clozapine (Cz), in a model of schizophrenia induced by ketamine (Ket) in mice. Neurobehavioral changes were examined after administration of Cp (1 or 5 mg/Kg, ip) or Cz (5 or 10 mg/Kg, ip), either alone or 30 minutes before Ket (10mg/kg, ip) in mice, and during oxidative stress after administration of the previous scheme including Vitamin E (Vit E) (400 mg/Kg) alone or 30 minutes before the Ket. Results showed that ketamine induced hyperlocomotion and increased the number of rearring and grooming events in the open field test and decreased the immobility time in the tail suspension test. Interestingly, these effects were blocked by Cp or Cz administration in the neurobehavioral tests. In addition to the behavioral changes, ketamine induced increase in lipid peroxidation, catalase activity and nitrite concentration. Again, either Cp or Cz reversed the effects of ketamine, this time on oxidative stress. In conclusion, these findings demonstrate effects similar to schizophrenia, antidepressant activity and pro-oxidative conditions induced by ketamine and reversal of these effects by Cp or Cz.